2007
DOI: 10.1128/aac.00338-07
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 30-Day Mortality among Patients with Pseudomonas aeruginosa Bloodstream Infections: Impact of Delayed Appropriate Antibiotic Selection

Abstract: Although a growing number of studies have found a relationship between delayed appropriate antibiotic therapy and mortality, few have attempted to quantify the temporal association between delayed appropriate antibiotic therapy and mortality. This study was designed to measure the elapsed time associated with an increased risk of 30-day mortality among patients with Pseudomonas aeruginosa bacteremia. The retrospective cohort study was conducted among immunocompetent, adult patients with P. aeruginosa bacteremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
197
4
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 293 publications
(225 citation statements)
references
References 20 publications
10
197
4
8
Order By: Relevance
“…Previously reported risk factors for mortality in patients with P. aeruginosa bacteremia include age, severity of illness (acute physiology and chronic health evaluation and SOFA scores), underlying comorbidities (malignancy, liver disease, and renal failure), and initial site of infection (23)(24)(25). Our results showed significant associations of a higher SOFA score and malignancy with mortality.…”
Section: Discussionsupporting
confidence: 60%
“…Previously reported risk factors for mortality in patients with P. aeruginosa bacteremia include age, severity of illness (acute physiology and chronic health evaluation and SOFA scores), underlying comorbidities (malignancy, liver disease, and renal failure), and initial site of infection (23)(24)(25). Our results showed significant associations of a higher SOFA score and malignancy with mortality.…”
Section: Discussionsupporting
confidence: 60%
“…Pseudomonas aeruginosa is the major pathogen implicated in sepsis and pneumonia [77,78]. Total phenylethanoid glycosides (TPG) from Monochasma savatieri prolonged survival rate of mice with P. aeruginosa or Staphylococcus aureus infection-induced sepsis in vivo.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…The inadequacy of empirical antimicrobial treatment has been shown to predict mortality in patients with bloodstream infection and severe sepsis, and it is more likely to occur in BSIs caused by antibiotic resistant bacteria. 2,3,7 In addition, we have previously demonstrated that IIAT was the strongest independent predictor of 30-day mortality in patients suffering from hematologic malignancies with BSIs caused by E. coli, 4 despite prompt administration of empirical broad-spectrum antibacterial therapy as recommended by the current clinical practice guidelines for the management of high-risk febrile neutropenic patients with cancer.…”
mentioning
confidence: 98%